Integración económica México-Estados Unidos y su aprovechamiento regional en México - Leonardo Egidio Torre Cepeda; Joana Cecilia Chapa Cantú; Eva Edith González González (Banco de México, 2020)
– Based on the World Input-Output Matrix 2016 estimated by Timmer et al. (2016), the Hypothetical Extraction Method is applied in a multi-country context to estimate Mexico's gross output and value added linked to the economic activity of the United States; and then the gross output and value added of the United States linked to Mexico's economic activity. Next, it is shown based on the Ghosh Regional Model how the value added of Mexico linked to the economic activity in the United States is allocated among its sectors and regions. The results capture the strong economic linkage between both economies at the aggregate level, as well as its sectoral concentration. The results also indicate that the Northern and Central regions of Mexico are those with the strongest link to the United States; followed by the Southern region, where the largest share of the oil industry is located.
Keywords: R11; R12; R15; 330; Hypothetical Extraction; Ghosh Input-Output Model; World Input-Output Matrix; Mexico; United States; Economic Integration